2015
DOI: 10.1037/rep0000064
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to satisfaction with life in veterans with mild traumatic brain injury.

Abstract: These results indicate the importance of properly identifying and treating symptoms of posttraumatic stress in veterans with a history of mTBI, as posttraumatic stress symptoms appear to be strongly related to SWL in those with a history of mild TBI. Optimizing sleep quality and social support may also be important in improving SWL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…41,42 Although social support has been found to be associated with satisfaction with life, our results indicate it does not mediate the relationship between social support and PTSD. 43,44 Kong et al 42 also found that gratitude led to social support. In this case, social support mediated the association between gratitude and satisfaction with life, thru high self-esteem.…”
Section: Discussionmentioning
confidence: 98%
“…41,42 Although social support has been found to be associated with satisfaction with life, our results indicate it does not mediate the relationship between social support and PTSD. 43,44 Kong et al 42 also found that gratitude led to social support. In this case, social support mediated the association between gratitude and satisfaction with life, thru high self-esteem.…”
Section: Discussionmentioning
confidence: 98%
“…1,8 Symptoms can include headaches, mood changes, fatigue, and memory issues, as well as problems with attention and concentration, and have been shown to affect satisfaction with life; this also occurs in veteran populations. 5 Although a percentage of survivors of TBIs become disabled as a result, Davis, et al 9 cites a 2009 review by McCrea, et al, 10 which stated that-at least in the case of a single mild TBI (mTBI) without complicationsthe large majority of cases have complete recovery within days to weeks.…”
Section: Introductionmentioning
confidence: 99%
“…4 In both civilian and military populations, these estimates are often thought to be low, as TBI can be underreported and/or misdiagnosed, given some symptoms can also mimic or overlap with symptoms of other diagnoses such as post-traumatic stress disorder (PTSD). [5][6][7] TBI symptoms, presentation, and recovery can vary greatly, depending on the severity of the injury, part(s) of the brain that are injured, and type of injury sustained, among other factors. 1,8 Symptoms can include headaches, mood changes, fatigue, and memory issues, as well as problems with attention and concentration, and have been shown to affect satisfaction with life; this also occurs in veteran populations.…”
Section: Introductionmentioning
confidence: 99%
“…In general, several variables that disabled veterans have, played an important role in disabled veterans' current satisfaction with life and hopelessness. Several studies show that there is a significant relationship between socio-demographic, occupational traits and satisfaction with life and hopelessness (Tuncay & Musabak, 2015;London, Heflin, & Wilmoth, 2011;Matarazzo et al, 2014;Mroczek & Spiro III, 2005;Seidl et al, 2015;Seligowski et al, 2012;Violanti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%